Effect of carbonization methods on the properties of tea waste biochars and their application in tetracycline removal from aqueous solutions. (March 2021) - Li, Bin; Zhang, Yin; Xu, Jin; Mei, Yanglu; Fan, Shisuo; Xu, Huacheng
Abstract: The properties of biochars and their adsorption performance are highly dependent on the carbonation methods. In this study, five carbonation methods, namely, hydrothermal treatment (HT), direct carbonization (BC), carbonization of hydrochar (HBC), KHCO3 activation carbonation (KBC), and KHCO3 activation carbonation of hydrochar (KHBC), were adopted to prepare tea waste biochars. Adsorption behaviors and mechanisms toward tetracycline (TC) by biochar in the aquatic environment were investigated. The results showed that carbonation methods significantly influence the morphology, carbon structure, chemical composition, and functional groups of the biochars based on the characterization of surface area and pore volume analysis, Fourier Transform Infrared Spectroscopy, Raman spectrum, Scanning Electron Microscope, Transmission Electron Microscope, X-ray photoelectron spectroscopy, X-Ray Diffraction, and elemental analysis. Combination of hydrothermal treatment with KHCO3 activation can significantly increase the surface area and enlarge the pore structure of biochar (KHBC and KBC). The BET of KHCO3 -activated BCs nearly increased 280 times (KHBC: 1350.80 m 2 g −1 ; KBC: 1405.06 m 2 g −1 ). BET, total pore volume and micropores volume of biochar has a positive influence on TC adsorption capacity. In addition, all adsorption processes can be well fitted by Langmuir and pseudo-second-order kinetic models. The maximum adsorption capacity of KHCO3 -activated BCs nearly increased approximately 40 times (KHBC: 451.45 mg g −1 ; KBC: 425.17 mg g −1 ). The dominant mechanisms of biochar-adsorbed TC were pore-filling effect and π–π interactions, followed by hydrogen bonds and electrostatic interactions. Therefore, KHBC has the potential to act as sorbents for TC removal from aquatic environment. Highlights: Five carbonation methods were adopted to produce tea waste biochar. Combination hydrothermal treatment with KHCO3 activation to biochar was effective. The maximum adsorption capacity of KHBC toward TC was 451.49 mg·g −1 . Pore-filling and π–π interactions were the dominant mechanisms for TC removal.